High levels of microparticles release from biodegradable polylactic acid paper cups compared with polyethylene-lined cups - Li, Dunzhu; Xiao, Liwen; Boland, John (My University, 2023)
Polylactic acid (PLA) is a popular replacement for conventional fossil-fuel based plastics products such as polyethylene (PE) due to its high biodegradability and recyclability. Previous studies confirmed that PLA microplastics (MPs) and PE MPs pose similar toxicity risks due to that MPs’ risk is primarily attributed to physical and indirect nutritional effects. Surprisingly, despite the widespread use, there have been very few studies of microparticles released from daily products made of biodegradable materials. We investigated release levels from eight single-use paper cups (SUPCs) lined with PLA and PE film. Under typical hot-beverage preparation conditions, the total number of particles released from PLA SUPCs was 4.2 times higher than that from PE SUPCs, with total numbers of 180,000 ± 31,000 and 43,000 ± 10,000 particles per litre, respectively. 22,000 ± 6,000 MPs were released per litre from PLA, which was 3.6 times the level of MPs released from PE SUPCs. In addition, significant levels of cellulose microfibres were released from PLA SUPCs, with quantities of 38,000 ± 31,000 microfibres per litre, while no such fibres were released from PE SUPCs. It should be noted that the levels of these particles may be underestimated due to the exclusion of nanoparticles (less than 0.8 μm, filter’s pore size), unidentified microparticles with high fluorescence backgrounds and attachments between different types of particles. In summary, a proportionately higher level of release of additive microparticles together with the release of cellulose microparticles are the key difference between biodegradable plastics like PLA and conventional plastic such as PE. Cellulose blending in manufacturing is likely related to higher MPs release from PLA cups than PE cups. Therefore, it is highly recommended to re-assess the manufacturing process, potential health and environmental risks of biodegradable plastic products as well as the formulation of related policies.
PUBLISHED
Keywords: Polylactic acid (PLA); high biodegradability; hot-beverage preparation; Microplastics; Biodegradable plastics; Polyethylene Single-used paper cups